Recovery of zinc and zinc oxide from zinc dross and sal almmoniac - Abon, Edgardo B. (College of Engineering, 1973)
Plant: Zn recovery plant -- Site: Pasig, Rizal -- Plant site area: 9,800 sq. ft. -- Raw materials: Zinc dross and Sal-Ammoniac -- Plant capacity: 16 tons/day -- Fixed capacity: 1,127,579 -- Total product cost: 957,262 -- Total capital investment: 1,296,716 -- Annual sales at maximum production: 1,235,731 -- Profit before taxes: 278,649 -- Profit after taxes: 200,229 -- Percent rate of return based on maximum production before taxes: 24.8% -- Percent rate of return based on maximum production after taxes: 17.8% -- Break-even point: 63% -- Shut-down point: 3% -- Pay-out time before taxes: 2.84 years -- Pay-out time after taxes: 3.60 years